2014
DOI: 10.1007/s00484-014-0874-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance of soil arthropods in relation to meteorological and edaphic factors in the agroecosystems of Faisalabad, Punjab, Pakistan

Abstract: Soil arthropods are an important component of agroecosystems, contributing significantly to their biodiversity and functioning. However, seasonal patterns, population dynamics, and significant roles of these soil arthropods in improvement of soil structures and functions are influenced by many factors. The objective of the current study was to investigate soil arthropod abundance in relation to a blend of meteorological and edaphic factors and to find out the difference in abundance among various crops (sugarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…But the correlation of Mg is reported against their observations. In another investigation by (Shakir & Ahmed 2015) on influence of blend of meteorological and edaphic factors on soil arthropod abundance observed that soil temperature and soil organic matter showed significant positive correlation with abundance, which supports the present findings. They also discussed that soil moisture and pH showed no significant correlations, which is applicable to the reported observations also.…”
Section: Influence Of Soil Properties On Shannon Diversity Indexsupporting
confidence: 80%
“…But the correlation of Mg is reported against their observations. In another investigation by (Shakir & Ahmed 2015) on influence of blend of meteorological and edaphic factors on soil arthropod abundance observed that soil temperature and soil organic matter showed significant positive correlation with abundance, which supports the present findings. They also discussed that soil moisture and pH showed no significant correlations, which is applicable to the reported observations also.…”
Section: Influence Of Soil Properties On Shannon Diversity Indexsupporting
confidence: 80%
“…Our aim was to determine whether the long-term green manure practice and seasonality alters soil macroarthropod community structure in an agroecosystem of the Brazilian semi-arid. Based on the studies developed by Vasconcellos et al (2010), Shakir and Ahmed (2015), and Bento et al (2016), evaluating seasonal variation of soil macroarthropods in semi-arid conditions, we expected to find variation in abundance and diversity of macroarthropod group in our study conditions. To accomplish this, we performed a field experiment and sampled soil macroarthropods in the rainy and dry seasons of an agroecosystem with long-term cultivation of plant species used as green manure in the Brazilian semiarid.…”
Section: Introductionmentioning
confidence: 94%
“…However, the textural properties of the clay loam soil probably also contributed, as its polyhedral or blocky structure (McKenzie et al, 1999) meant that habitable pore space was available for microarthropods. Results from our pot experiment also showed that more microarthropods were recovered from the clay loam soil than a much lighter-textured sandy loam, again emphasising the fact that a soil's textural properties and carbon levels influence microarthropod abundance (Vreeken-Buijs et al, 1998;Larsen et al, 2004;Shakir and Ahmed, 2015).…”
Section: Discussionmentioning
confidence: 54%
“…Although sugarcane is the most important agricultural crop in tropical and sub-tropical regions of Australia, and a major crop worldwide, the soil microarthropod fauna of cane fields is little studied. Most research has concentrated on the biology and control of relatively large root-feeding pests such as cane grubs and soldier flies, on a few smaller pests such as ground pearls and symphylans, or on arthropod communities at a low level of taxonomic resolution (Allsopp et al, 1993;Sajjad et al, 2012;Shakir and Ahmed, 2015; but see Asif et al, 2016, on Collembola). In this paper we present survey results that show that sugarcane soils, at least those that have not been tilled for several years, contain a diverse community of microarthropods with the potential to improve crop health through their role in cycling nutrients and regulating populations of root pests and pathogens.…”
Section: Introductionmentioning
confidence: 99%